2016
DOI: 10.1038/nature17175
|View full text |Cite
|
Sign up to set email alerts
|

Quantum hydrogen-bond symmetrization in the superconducting hydrogen sulfide system

Abstract: The quantum nature of the proton can crucially affect the structural and physical properties of hydrogen compounds. For example, in the high-pressure phases of H2O, quantum proton fluctuations lead to symmetrization of the hydrogen bond and reduce the boundary between asymmetric and symmetric structures in the phase diagram by 30 gigapascals (ref. 3). Here we show that an analogous quantum symmetrization occurs in the recently discovered sulfur hydride superconductor with a superconducting transition temperatu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
307
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(344 citation statements)
references
References 41 publications
36
307
0
1
Order By: Relevance
“…Theoretical studies, which have shown that the superconductivity observed in Ref. [38] arises primarily from an H 3 S phase [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] whose structure has been recently confirmed experimentally [56], will not be described within this short review. We will, however, discuss the results of first principles calculations carried out for the hydrides of phosphorus [57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies, which have shown that the superconductivity observed in Ref. [38] arises primarily from an H 3 S phase [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] whose structure has been recently confirmed experimentally [56], will not be described within this short review. We will, however, discuss the results of first principles calculations carried out for the hydrides of phosphorus [57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…113 As mentioned above, the cubic Im3m structure of H 3 S responsible for the very high T c in H 3 S is stabilized down to considerably lower pressures when anharmonic quantum nuclear zero-point motion is included. 19 Both lithium at low pressures and H 3 S-Im3m at high pressures are close to structural instabilities. Matthias emphasised the importance of structural symmetry in determining superconducting T c 's, 114 and empirical observations suggest that cubic symmetry is particularly efficacious.…”
Section: A Glimpse Of the Futurementioning
confidence: 99%
“…Very recently, Errea et al 19 have demonstrated that the quantum hydrogen-bond symmetrization that occurs on formation of H 3 S-Im3m is responsible for the very high T c . They have also shown that anharmonic vibrations stabilise this structure down to lower pressures than would be obtained within the harmonic approximation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Their finding appears to vindicate the BCS theory because Tian Cui and his team had used the theory 3 to predict the record-breaking high T c before the experiment by Eremets and colleagues, and Ion Errea and coworkers later verified Cui and coworkers' results theoretically. 4 Both groups used the McMillan formula (derived from a generalized version of BCS theory), which relates T c to the electron-phonon coupling strength and the Coulomb pseudopotential, a measure of the Coulomb repulsion between electrons.…”
mentioning
confidence: 99%